Review on Adsorption of Heavy Metal in Wastewater by Using Geopolymer - Ariffin, Nurliyana; Abdullah, Mohd Mustafa Al Bakri; Mohd Arif Zainol, Mohd Remy Rozainy; Murshed, Mohd Fared; Zain, Hariz; Faris, Meor Ahmad; Ridho, Bayuaji (EDP Sciences, 2017)
Rapid development of advanced technology in Malaysia gave impact increasing in the accumulation of heavy metal every day in our daily life through wastewater. Long term exposure of human bodies to heavy metals susceptible to receives various infections and diseases. From an environmental and economic perspective, adsorption is acceptable process that can be applied in wastewater treatment. However, usage of activated carbon most acknowledged and costly adsorbents lead people to find an alternative to activated carbon. Several studies of physical properties of geopolymer make them gain attention to replace an activated carbon in the treatment of heavy metal. This paper review adsorption of heavy metal by using geopolymer.